Analysis Of Innovation Activity Of Commercial Banks Of The Republic Of Uzbekistan - Minarova Murshida Khozhimuratovna (Periodica Journal, 2025)
This article examines the current state and development prospects of innovative activity in the commercial banking sector of Uzbekistan. Drawing upon statistical data, empirical surveys, and comparative analysis, the study assesses the level of digitalization, investment in financial technologies, mobile banking usage, and customer satisfaction across five major commercial banks. Findings indicate that Asaka Bank and the National Bank are leading in terms of digital innovation, driven by strong fintech collaborations and technological investment. The article also highlights regional disparities in digital access and identifies key factors influencing customer adoption. Based on the results, strategic policy recommendations are proposed to accelerate the digital transformation of Uzbekistan’s banking system, enhance financial inclusion, and strengthen fintech ecosystems. The research contributes to understanding the dynamics of financial innovation in emerging markets, using Uzbekistan as a case study.
Keywords: Commercial banks; innovation; digital banking